Factors influencing health service utilization among 19,869 China’s migrant population: an empirical study based on the Andersen behavioral model - Yalin Song; Jingru Liu; Shuming Yan; Mingze Ma; Clifford Silver Tarimo; Clifford Silver Tarimo; Yiyang Chen; Yanhong Lai; Xinghong Guo; Jian Wu; Beizhu Ye (Frontiers in Public Health)
BackgroundWith the surge in population migration across China, particularly from rural to urban regions, the migrant population encounters unique challenges in accessing healthcare services. This study addresses the gap in health service utilization among migrants, specifically examining their engagement with basic public health services and the factors that impact these interactions.MethodsIn the year 2023, a cross-sectional survey was carried out among 19,869 migrants in China, employing a multi-stage stratified sampling technique for participant recruitment. The analysis was guided by the Andersen Health Service Utilization Model, examining predisposing, enabling, and needing factors related to health service utilization. Chi-square test and multivariate logistic regression were used to explore the group difference and the associations between demographic characteristics and utilization of health service.ResultsThe study revealed significant underutilization of health services among the migrant communities, with only a minority having established health records or engaged with family doctors. Additionally, there existed a notable disparity in health education and the proactive pursuit of health knowledge. Age, gender, educational level, socioeconomic status, employment status, and proximity to healthcare facilities significantly influenced health service utilization. Notably, healthier lifestyle choices correlated with the increased involvement in health services.ConclusionThe findings highlight a substantial need for targeted health policy interventions and healthcare system reforms to enhance the accessibility and utilization of health services among the migrant population in China. Promoting education on health services, improving healthcare infrastructure, and addressing the unique needs and barriers encountered by migrants are crucial measures for achieving equitable health outcomes.